A Victorian Curate A Study of the Life and Career of the Rev. Dr John Hunt - Yeandle, David (Open Book Publishers, 2021)
"The Rev. Dr John Hunt (1827-1907) was not a typical clergyman in the Victorian Church of England. He was Scottish, of lowly birth, and lacking both social connections and private means. He was also a witty and fluent intellectual, whose publications stood alongside the most eminent of his peers during a period when theology was being redefined in the light of Darwin's Origin of Species and other radical scientific advances. Hunt attracted notoriety and conflict as well as admiration and respect: he was the subject of articles in Punch and in the wider press concerning his clandestine dissection of a foetus in the crypt of a City church, while his Essay on Pantheism was proscribed by the Roman Catholic Church. He had many skirmishes with incumbents, both evangelical and catholic, and was dismissed from several of his curacies. This book analyses his career in London and St Ives (Cambs.) through the lens of his autobiographical narrative, Clergymen Made Scarce (1867). David Yeandle has examined a little-known copy of the text that includes manuscript annotations by Eliza Hunt, the wife of the author, which offer unique insight into the many anonymous and pseudonymous references in the text. A Victorian Curate: A Study of the Life and Career of the Rev. Dr John Hunt is an absorbing personal account of the corruption and turmoil in the Church of England at this time. It will appeal to anyone interested in this history, the relationship between science and religion in the nineteenth century, or the role of the curate in Victorian England. "